Mastering Economic Terminology And Development Of Professional Speech - Abdusaidova Gulkhayo Bakhriddin qizi (Euro Asian Journal Publishing, 2025)
Effective conversation is a cornerstone of expert competence in the discipline of economics. Mastering monetary terminology is fundamental no longer solely for tutorial success however additionally for expert increase in world financial environments. This article explores the function of monetary terminology in fostering unique and persuasive financial discourse. It additionally examines techniques for growing expert speech in financial contexts, thinking about each theoretical insights and realistic applications. The findings advocate that centered linguistic training, contextual learning, and interdisciplinary tactics extensively decorate monetary communication
Keywords: Economic terminology; professional speech; economics education